2017
DOI: 10.1016/j.bmc.2016.10.035
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of central penetration from a peripherally administered oxytocin receptor selective antagonist in nonhuman primates

Abstract: The physiology of the oxytocin receptor has increasingly become a focus of scientific investigation due to its connection with social behavior and psychiatric disorders with impairments in social funciton. Experimental utilization of small molecule and peptide antagonists for the oxytocin receptor has played a role in deciphering these biological and social behavior connections in rodents. Described herein is the evaluation of a potent and selective oxytocin receptor antagonist, ALS-I-41, and details to consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A potential alternative for future studies is to make use of recently available selective antagonists which penetrate into the CSF (Smith et al, 2017). When combined with precise microinjection techniques it would be possible to selectively block OT receptors in various brain regions, and assess both behavioral and neurophysiological changes induced by IN, AE, or peripheral administration of OT.…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential alternative for future studies is to make use of recently available selective antagonists which penetrate into the CSF (Smith et al, 2017). When combined with precise microinjection techniques it would be possible to selectively block OT receptors in various brain regions, and assess both behavioral and neurophysiological changes induced by IN, AE, or peripheral administration of OT.…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%
“…As previously described, rodents and NHPs show considerable differences in the expression and pharmacological properties of OXTRs, which limits our ability to extrapolate findings from rodents to humans and NHPs. A potential alternative for future studies is to make use of recently available selective antagonists which penetrate into the CSF (Smith et al, 2017). When combined with precise microinjection techniques it would be possible to selectively block OT receptors in various brain regions, and assess both behavioral and neurophysiological changes induced by IN, AE, or peripheral administration of OT.…”
Section: Studies Of Oxytocin In Non-human Primatesmentioning
confidence: 99%
“…There is a substantial need for the discovery of specific radio-ligands, small antagonists, or agonists of OTR that could penetrate the brain and that we can use to image OTR in vivo in the human brain using positron emission topography. Our group evaluated a potent and selective oxytocin receptor antagonist in nonhuman primate and showed that it mildly penetrated the brain (Smith et al 2016). These results are promising and further research on small potent molecules that penetrate the brain can be important to pursue in the human population.…”
Section: Oxytocin System Origin Structure Synthesis and Releasementioning
confidence: 99%
“…14,15 For in vivo SPECT imaging, Gallium-67 labelled OT has been reported. 16 Recently, several candidate molecules were evaluated for in vivo imaging of the central OTR; [17][18][19][20][21][22] however, despite some encouraging in vitro results, PET imaging studies showed either no significant brain uptake or a limited CNS distribution that did not correspond to the expected OTR distribution.…”
Section: Introductionmentioning
confidence: 99%